La fundamentación de la Casación Civil como recurso extraordinario y su admisibilidad. - Vélez García, Lucíla Andrea (2022)
The present investigative work entitled "The Foundation of the Civil Cassation as an extraordinary appeal and its admissibility", examines the legal incidents derived from the admissibility of the civil appeal and its justification; considers the formal and material requirements that the document, requesting the admission of the civil cassation appeal, must contain to achieve its admissibility, by the associate judges of the National Court of Justice. We will address the conceptualization of the nullities terms, motivation, vices and the rules of substantive law; in addition to the analysis of the jurisprudential line of the Constitutional Court regarding the civil appeal contained in two sentences, which are critically analyzed at the end of this investigative work.